Collectivism and Climate Influence: Interpreting Indonesian Society Through the Perspective of Ibn Khaldun - Iman, Hafidz; Muhtar, Mohamad Khusnial; Rohman, Ahmad Fatkhur (Universitas Islam Negeri Sumatera Utara, 2025)
This study analyzes the influence of climate on the formation of social character in Indonesian society based on Ibn Khaldun’s theory. In the Muqaddimah, Khaldun argues that hot and warm climates foster collectivism through environmental adaptation. This research employs a philosophical approach and literature analysis to examine the relevance of this theory within the context of Indonesia’s tropical climate. The findings indicate that the collectivist character of Indonesian society, as seen in practices such as gotong royong (mutual cooperation), reflects an enduring adaptation to ecological challenges. The study also highlights how Indonesia’s agrarian traditions and communal resilience are rooted in climatic necessity. However, the growing impact of globalization and modernity is contributing to a shift toward individualism, disrupting traditional communal patterns. This dynamic tension between collectivist values and individualist tendencies presents new socio-cultural challenges. Ultimately, this study underscores the continued relevance of Ibn Khaldun’s environmental theory for interpreting Indonesia’s socio-cultural transformations and opens avenues for future interdisciplinary research that bridges philosophy, sociology, and climate studies.